THE IMPACT OF INTRINSIC AND EXTRINSIC MOTIVATION ON THE DEVELOPMENT OF PHYSICAL, SKILL, AND PSYCHOLOGICAL PERFORMANCE IN PROFESSIONAL FOOTBALL PLAYERS - Dr.Mushtaq Khadhim Mohammed (Proximus Journal Publishing, 2026)
This paper investigates the differential impact of intrinsic motivation (IM) and extrinsic motivation (EM) on the performance domains of professional football players: physical, skill-based, and psychological. Drawing on a narrative review and synthesis of empirical findings from recent literature, the study confirms that while EM (e.g., financial rewards, recognition) can yield short-term performance gains, IM (e.g., passion, enjoyment, self-determination) is fundamentally linked to sustained high performance, long-term commitment, and psychological resilience [1]. Empirical evidence from studies on elite football players demonstrates a significant correlation between high competence and intrinsic factors like passion [4]. Furthermore, the absence of motivation (amotivation) is shown to be a major predictor of stress and burnout [6]. The findings underscore the critical need for professional football organizations to adopt coaching strategies that cultivate IM to ensure optimal and sustained athlete development
Keywords: Motivation; physical performance; technical; psychological performance